Uterine Rupture Associated with Uterine Torsion in a Pregnant Bitch - Niwas, Ram; Jinagal, Sujata; Amandeep; Anil; Dutt, Ravi (The Indian Journal of Animal Reproduction, 2023)
Uterine torsion is an unusual and potentially serious problem in pregnant she-dogs. This case study documents the surgical management of uterine rupture associated with uterine torsion in a she-dog presented on the 68th day of pregnancy. Upon exploration of abdominal cavity, uterine torsion was observed over the uterine body and just adjacent to uterine torsion, there was rupture of the uterus. Therefore, laparahysterectomy was performed. The post-operative care included broad spectrum antibiotics, anti-histaminics, anti-inflammatory drugs and fluid therapy. The she dog had uneventful recovery.